The Role of The Tradition of Almsgiving in Strengthening Multicultural Islamic Educational Values - Ilahin, Nur (Jurnal Cendekia Media Komunikasi Penelitian dan Pengembangan Pendidikan Islam, 2025)
This study aims to determine the role of the tradition of almsgiving in strengthening the values of multicultural Islamic education. The approach used was a qualitative ethnographic approach, while data were collected through observation, interviews, and documentation. Data analysis techniques involved data reduction, data display, and drawing conclusions. The research findings revealed that the tradition of almsgiving is closely related to the values of multicultural Islamic education because it can strengthen ties, build tolerance, create harmony, uphold justice, and foster a spirit of togetherness. This relationship is evident in various almsgiving practices, such as ngaturi activities at celebrations, funeral feasts, nyadran, and qurban. The impacts of this relationship between the tradition of almsgiving include the role of religious leaders in preserving traditions, its function as an educational tool for children to learn to give alms from an early age, instilling the values of generosity and caring, strengthening social equality, respect for the services of ancestors, and its potential to improve community welfare. This research contributes to integrating Islamic educational values with the tradition of almsgiving, especially in the context of multicultural societies, thereby strengthening social harmony and enriching the practice of Islamic education in plural societies.